(untitled) (Clepsidra - Interdisciplinary Journal of Memory Studies, 2022)
In this paper we analyze from a conceptual and operational perspective some situations that invite us to think about the deployment of politics of memory in times where politics is affected by the logic of the so-called anti-politics. We present, in the first place, a theoretical-methodological perspective of approaching the category ‘politics of memory’ and then we carry out a brief historical review of those politics in Argentina. Finally, we review some situations that impacted the public space and generated high reaching reactions aimed at reestablishing the limits of what can be said. These episodes took place within the framework of the emergence of so-called anti-political rhetoric, but also of the ways in which this rhetoric is used in the right-wing redefinition of the democratic consensus that followed the last military dictatorship.